Major and trace elements redistribution in weathered claystones from the Corumbatai Formation, Parana Sedimentary Basin, Sao Paulo, Brazil - Godoy, Leticia Hirata [UNESP]; Sardinha, Diego de Souza; Torres Moreno, Maria Margarita [UNESP] (Soc Brasileira Geologia, 2017)
We studied 30 samples from 10 mining fronts of clayish rocks of the Corumbatai Formation, in the region of the Santa Gertrudes Ceramic Pole (Sao Paulo, Brazil), in order to evaluate the variation of rare earth elements (REE), mineralogy, weathering effects and provenance. The profiles show diagnostic geochemical signatures that are uniform across the Corumbatai Formation samples in the studied region and can be correlated from mine to mine, i.e.: 1) the constant MgO/K2O ratio and the variation of other oxides, which allow the identification of three main groups of samples; 2) similar groups of chemical index of weathering (CIW) and chemical index of alteration (CIA); 3) the immobile character of REE, Th, and Sc. The erosion/denudation processes were apparently the same among the studied profiles, allowing the identification of a similar weathering pattern among the mines, despite its location within the stratigraphic column. Mineralogical and geochemical data here reported suggest a dominant felsic source, but intermediate or mixed sources cannot be discarded. The chemical and mineralogical aspects observed are practically uniform along the studied profiles and mines, which allow them to be used as raw material by the industries of the Santa Gertrudes Ceramic Pole (SGCP) region.
Keywords: weathering; remobilization; sedimentary rocks; geochemistry; Parana Basin; ceramic